I spy ultimate challenger! : a book of picture riddles - Wick, Walter; Marzollo, Jean. (New York : Scholastic Inc., 2003)
Rhyming text leads the reader to find objects hidden in the photographs.
The rainbow express -- Arts & crafts -- Baking cookies -- A is for-- -- The treasure chest store -- Clown dressing room -- Good morning -- Sorting and classifying -- Santa$1 (Bs workshop -- Toy planet -- The secret note -- Inventor$1 (Bs workshop -- Extra credit riddles.s
"Cartwheel books."
Keywords: Picture puzzles -- Juvenile literature; Picture puzzles